Sing backwards and weep : a memoir - Lanegan, Mark; Shubaly, Mishka (London : White Rabbit, 2020)
When Mark Lanegan first arrived in Seattle in the mid-1980s, he was just 'an arrogant, self-loathing redneck waster seeking transformation through rock 'n' roll.' Little did he know that within less than a decade, he would rise to fame as the front man of the Screaming Trees, then fall from grace as a low-level crack dealer and a homeless heroin addict, all the while watching some of his closest friends rocket to the forefront of popular music. In 'Sing Backwards and Weep', Lanegan takes readers back to the sinister, needle-ridden streets of Seattle, to an alternative music scene that was simultaneously bursting with creativity and dripping with drugs.
englanti
vastat
KIRJA / BOK
Keywords: Lanegan, Mark; Screaming Trees (yhtye); muusikot; laulajat; rock; Yhdysvallat; elämäkerrat; muistelmat